Calculation of Steel Pipeline Corrosion Depth for Various Conditions of Electrolyte Solutions in Cracks - Stepova, Olena; Homenko, Anna; Roma, Valerii (International Journal of Engineering and Technology, 2018)
On the basis of the electrochemical corrosion mathematical pipeline model in the insulating coating crack under the action of an aggressive electrolytic medium towards the pipeline metal, theÂ dependence was obtained that allowsÂ to calculate the pipeline wall corrosion depth of the during the work of macro-galvanic corrosion couples in the conditions of stable and periodic stay of the aggressive solution in the damaged zone. The advantage of this model is the ability to predict the corrosion development over time regardless the corrosive electrolyte chemical composition, the possibility of obtaining necessary design parameters for operated structures. The developed dependencies of the pipeline section Ñorrosion depth make it possible to plan rationally the repair work, to predict the structure work real terms, to review the operation mode, etc. The obtained results allow us to more reliably evaluate the bearing capacity of structures that operateÂ in conditions of aggressive medium with cracks.Â Â